1992
DOI: 10.1111/j.1440-1673.1992.tb03162.x
|View full text |Cite
|
Sign up to set email alerts
|

Primary Squamous Cell Carcinoma of the Breast

Abstract: A patient with pure primary squamous cell carcinoma (SCC) of the breast is reported. The patient was a 72 year old female who presented with a 4 month history of an enlarging left breast mass. Surgery involved a radical mastectomy and this was followed by post-operative radiotherapy and chemotherapy. The patient died of extensive metastatic disease some four months after surgery. The various characteristics of SCC of the breast are briefly discussed. A sub-group of SCC of the breast is identified among reporte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

1996
1996
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 10 publications
0
3
0
1
Order By: Relevance
“…6 Several reports have attributed SqCC with a more aggressive clinical course than IDC. 21 The rate of axillary lymph node metastases in primary SqCC is 22% (Table 1); we found no data to support the claim of higher rates by Weigel et al 1 By contrast, in IDC of the breast, rates as high as 40% to 60% have been reported at presentation. Additionally, lymphatic spread is recognized as the major pathway for dissemination of the disease: hence, the importance of axillary node dissection as a staging and therapeutic procedure.…”
Section: Natural Historymentioning
confidence: 62%
“…6 Several reports have attributed SqCC with a more aggressive clinical course than IDC. 21 The rate of axillary lymph node metastases in primary SqCC is 22% (Table 1); we found no data to support the claim of higher rates by Weigel et al 1 By contrast, in IDC of the breast, rates as high as 40% to 60% have been reported at presentation. Additionally, lymphatic spread is recognized as the major pathway for dissemination of the disease: hence, the importance of axillary node dissection as a staging and therapeutic procedure.…”
Section: Natural Historymentioning
confidence: 62%
“…Rosen and Ernsberger (1) reported 5‐year survival rates in their series of 40 patients with low‐grade adenosquamous carcinoma to be 68%, 64%, and 48% for stages I, II, and III, respectively, with overall 5‐year survival being 55%. The poor prognosis reported by others (18,19) may be a reflection of the advanced size of these tumors. Eggers and Chesney (5) and Eusebi et al (20) suggest that squamous cell carcinomas have an outcome similar to that of adenocarcinomas of a similar stage.…”
Section: Pathologic Molecular and Clinical Features Of The Six Mbc mentioning
confidence: 86%
“…As reported in the literature, PSCC of the breast is an exceedingly rare malignancy. Although it was firstly reported more than 100 years ago [ 11 ], most published studies were care reports or small retrospective cohorts from a single institution [ 2 , 5 8 , 12 , 13 ]. Therefore, the clinical characteristics and outcomes of PSCC of the breast are limited, although most researchers who achieved a relative consistent observation across many studies indicated that PSCC has aggressive histological features at presentation and has poor outcomes [ 14 ].…”
Section: Discussionmentioning
confidence: 99%